Inhibition of p38 mitogen activated protein kinase controls airway inflammation in cystic fibrosis. Issue 9 (30th June 2005) - Raia, V; Maiuri, L; Ciacci, C; Ricciardelli, I; Vacca, L; Auricchio, S; Cimmino, M; Cavaliere, M; Nardone, M; Cesaro, A; Malcolm, J; Quaratino, S; et al.
Abstract : Background: Cystic fibrosis (CF) airways are characterised by chronic inflammation, increased interleukin (IL)-8 secretion, and neutrophil activation which are considered the principal factors of morbidity and mortality in CF patients. Optimising management of this chronic inflammatory response is therefore a key issue of basic and clinical CF research. Several reports have addressed ways to manage CF airways inflammation, and an attractive therapeutic strategy may be the inhibition of the p38-mitogen activated protein kinase (p38-MAP-k) pathway. Methods: A new ex vivo model was used to study the mucosal inflammatory response to environmental airways stimuli. Nasal biopsy tissues from CF patients and controls were cultured ex vivo for 20 minutes, 4 hours, and 24 hours in the presence of lipopolysaccharide (LPS) from Pseudomonas aeruginosa (PA) with and without the p38-MAP-k inhibitor SB203580. Quantitative mRNA assessment, immunohistochemistry, and Western blots were used to detect the expression and modulation of inflammatory markers. Results: PA-LPS challenge induced a time dependent mucosal inflammation indicated by rapid epithelial activation, IL-8 release, COX-2 upregulation, and neutrophil migration to the upper mucosal layers. Some of these LPS induced changes (IL-8 release and neutrophil migration) were specific to CF tissues. SB203580 significantly controlled all LPS induced mucosal changes in CF tissues. Conclusion: These findings provide a rationale and proof of principle for the potential use of p38-MAP-k inhibitors to control inflammation in patients with CF.